2020
DOI: 10.1002/ctm2.172
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5 deficiency enhances the proliferative and therapeutic capacities of adipose‐derived mesenchymal stem cells via metabolic switching

Abstract: Background: Mesenchymal stem cells (MSCs) have therapeutic potential for multiple ischemic diseases. However, in vitro expansion of MSCs before clinical application leads to metabolic reprogramming from glycolysis to oxidative phosphorylation, drastically impairing their proliferative and therapeutic capacities. This study aimed to define the regulatory effects of Sirtuin 5 (SIRT5) on the proliferative and therapeutic functions of adipose-derived MSCs (ADMSCs) during in vitro expansion. Methods: ADMSCs were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…Upon exposure to hypoxia, the 2D-cultivated MSCs showed significantly upregulated expression of PDK1 and SLC2A1 and downregulated expression of G6PD and 6PGD (Figure 4C, p < 0.01), a clear indication of MSC metabolic remodeling toward glycolysis with a reduced pentose phosphate pathway. The observed metabolic shift was consistent with the findings reported in the literature [24,25]. For 3D MSC spheroids prepared under normoxia, however, changes in the mRNA levels were rather limited, while hypoxia-cultivated 3D MSC spheroids displayed a remarkable shift in the expression level of the investigated genes (Figure 4C, p < 0.05).…”
Section: The Enhanced Therapeutic Potential Of Mscs After Assembly Into a 3d Spheroid Configuration Is Not Fully Attributed To The Develosupporting
confidence: 91%
See 1 more Smart Citation
“…Upon exposure to hypoxia, the 2D-cultivated MSCs showed significantly upregulated expression of PDK1 and SLC2A1 and downregulated expression of G6PD and 6PGD (Figure 4C, p < 0.01), a clear indication of MSC metabolic remodeling toward glycolysis with a reduced pentose phosphate pathway. The observed metabolic shift was consistent with the findings reported in the literature [24,25]. For 3D MSC spheroids prepared under normoxia, however, changes in the mRNA levels were rather limited, while hypoxia-cultivated 3D MSC spheroids displayed a remarkable shift in the expression level of the investigated genes (Figure 4C, p < 0.05).…”
Section: The Enhanced Therapeutic Potential Of Mscs After Assembly Into a 3d Spheroid Configuration Is Not Fully Attributed To The Develosupporting
confidence: 91%
“…Conversely, the expression of G6PD and 6PGD was upregulated as the incubation time increased, indicating the effect of other niche factors, instead of hypoxia, inherent in the spheroids on the modulation of cellular metabolism. As an enhancement of the pentose phosphate pathway is reportedly associated with MSC survival and paracrine functionality [25,45], we speculated that metabolic reconfiguration upon spheroid assembly could be an important niche factor contributing to the enhanced therapeutic potential of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pieces of evidence have revealed the critical role of histone modification in regulating the transcription of cccDNA, particularly the acetylation and methylation of cccDNA-bound histone 3 (H3) and histone 4 (H4) ( Zhang et al, 2017 , p. 5; Ren et al, 2018 , p. 3). To investigate whether histone succinylation plays a potential role in the HBV life cycle, we used the RNA interference method to screen a series of the reported histone succinyltransferases and desuccinylases, including p300, KAT2A, CPT1A, SIRT5, and SIRT7 ( Figure 1A ), which are known to catalyse histone succinylation or desuccinylation to result in transcription activation or repression ( Zhang et al, 2011 ; Li et al, 2016 ; Wang et al, 2017 ; Kurmi et al, 2018 ; Ou et al, 2020 ). The data showed that the histone succinyltransferases and desuccinylases (including p300, KAT2A, CPT1A, SIRT5, and SIRT7) were efficiently knocked down ( Figure 1B and Supplementary Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…SIRT5 has been previously reported as a master metabolic regulator, and its expression levels are significantly associated with the metabolic patterns and functions of various cell types [ 34 ]. SIRT5 not only maintains mitochondrial function through posttranslational modifications of mitochondrial proteins and enzymes but also modulates different pathways, including glucose oxidation, ketone body formation, fatty acid degradation, ammonia disposal, and redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%